Preparation for the TEC World: Mathematical Logical Thinking Workshop - Brown-Richards, Enos E. (2019)
Encouraging the participation of women in engineering, technology and economic sciences is a major challenge for state universities, since as with most cases of gender inequality, an obstacle to overcome is the culture of negative opinions towards the abilities and qualities of the woman to perform successfully. They are joined by other groups such as Afro-descendants and indigenous people whose opportunities to enter these careers are also plagued by biases and prejudices. To mitigate this factor, it is necessary to generate conditions in which the minority groups, in this case, women, Afro-Costa Ricans and indigenous people, have in quantity and quality, better options to overcome the barriers to enter these careers with great mathematical content. The Aula Movil is an academic extension program that materializes the university-society bond and through which important scientific and cultural knowledge are generated and socialized, giving the academy the opportunity to respond and attrend strategically to local and national development from the needs identified in society.